Pengaruh Influencer dan Content Marketing terhadap Keputusan Pembelian Melalui Niat Beli Mahasiswa Pada Platform Shopee: Studi Kasus Shopee Video sebagai Media Pemasaran Digital: Penelitian - Mutiara Cantika Kamila Putri; Bambang Setyo Pambudi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research analyze the influence of influencers and content marketing on purchasing decisions through students’ purchase intentions on the Shopee platform, with a focus on the use of Shopee Video as a digital content marketing medium. The research employed a quantitative approach by distributing questionnaires to students who actively use Shopee Video, allowing the collected data to represent the behavior of young consumers who are familiar with short-video content.The findings show that influencers and content marketing have a positive and significant effect on purchase intention, which subsequently increases purchasing decisions. These results emphasize that credible influencers and appealing video content can strengthen consumer enhance interest, and encourage purchasing behavior. Furthermore, the study provides insights into how content characteristics, influencer communication styles, and short-video consumption patterns influence consumers’ psychological processes, from attention to purchasing actions. Therefore, the results of this study can be utilized by businesses to optimize more effective digital marketing strategies that align with current consumer behavior trends.